2019
DOI: 10.1002/14651858.cd001118.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Print-based self-help interventions for smoking cessation

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 219 publications
1
25
0
2
Order By: Relevance
“…Self-help interventions are efficacious for smoking cessation, with potentially high reach at low cost. 28 The economy of the targeted intervention yielded a cost per quitter lower than most smoking cessation interventions, 29 particularly when excluding smokers with low dependence. Costs might be reduced substantially by using a mobile health format, which would also enable more frequent contact over a longer duration of treatment.…”
Section: Low Cigarette Dependencementioning
confidence: 99%
“…Self-help interventions are efficacious for smoking cessation, with potentially high reach at low cost. 28 The economy of the targeted intervention yielded a cost per quitter lower than most smoking cessation interventions, 29 particularly when excluding smokers with low dependence. Costs might be reduced substantially by using a mobile health format, which would also enable more frequent contact over a longer duration of treatment.…”
Section: Low Cigarette Dependencementioning
confidence: 99%
“…Quitlines provide smoking cessation support including telephone counselling and written materials ( Livingstone‐Banks et al, 2019 ; Matkin et al, 2019 ). Through quitlines, telephone support and written materials can reach large populations ( Zhu et al, 2002 ) and particular populations such as young people ( Cummins et al, 2007 ) and those living in rural areas ( Sheffer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients may benefit from specific counseling on how continued smoking affects their cancer treatment and outcome. Regardless of the approach, numerous studies have shown that the delivery of a pamphlet on smoking cessation (as is the current standard of care in many surgical oncology clinics including this institution) is only marginally better than no intervention at all . However, because our data also suggest that this patient population exhibits feelings of hopelessness and/or a lack of desire to quit tobacco it is crucial to distinguish between patients who are actually interested in smoking cessation treatment so as not to waste time and resources.…”
Section: Discussionmentioning
confidence: 80%